Rancang Bangun Prototipe Aplikasi Wireless Sensor Network untuk Peringatan Dini Terhadap Banjir - Nugroho, Budi Hari; Jusak, Jusak; Susanto, Pauladie (Journal of Control and Network Systems, 2014)
Frequent floods occurred in several areas in Indonesia annually that eventually cause who are affected by the flood. More often floods arrive at night when most people were fast asleep. This means that people are mostly not ready when disaster comes. This is one of the reasons why long-range early-detection flood device was designed. Not only to improve the accuracy of detection of the flooding but it will be able to monitor so there will be an accurate precaution signal of this disaster at the right time. Monitoring the water level of the river situation in real time using Wireless Sensor Network (WSN) technology. WSN is a wireless network infrastructure that uses sensors to monitor physical or environmental conditions that are connected to the network. In this study, each node in the WSN consists of the Arduino Uno microcontroller modules, XBee series 2 as wireless communications, and PING ultrasonic sensor and RTC (Real Time Clock). Base on our examination the WSN technology for early warning of flooding detection is able to produce a system that allows people predict the possibility of flooding. Water level measurements with PING ultrasonic sensor has an error percentage between 2.09% to 2.56%. The results show that the system is able to work well with a 97.44% accuracy